Structure of AFP commissions: collection alternatives and their effects - González Araya, Marcelo; Clavero Díaz, Christopher (Estudios de Administración, 2013)
The current pension system design considers the collection of fees by the administration of the various accounts held by the affiliates. The mandatory deposit regular contributions in theindividual capitalization account (additional contribution) is set as a percentage of remuneration or taxable income that gives rise to the contribution, representing the main source of incomeof the AFP (86% on average for the 2002-2012 period). As a result of such a scheme of income, generally there are asymmetries in the returns of the participants in the system, producing negative perceptions in turn focused on radical changes in the model. Following this, a constant source of discussion is the commission rate used and its levels. In this regard, billing system modifications are often not free from tensions. To those objectives sought by the regulator, as are usually the universal coverage and greater degrees of competition the incentive effects of contributors and administrators are added. This study aims to analyze the impact of a possible change in the commission structure, considering both the point of view of the industry –operational results and income statements– as the point of view of affiliates –total balance and payment of commissions–. Additionally, a proposed fee structure that would improve the final pension, without altering the current results of the AFP is delivered.